Tourism Potential in Medan City with an Inclusive Digital Marketing Approach - Parinduri, Rizka Elvira (International Journal Of Education, Social Studies, And Management (IJESSM), 2025)
Medan City's tourism potential stems from its natural beauty, historical heritage, diverse population, strategic location, diverse customs, culture, and adequate infrastructure. Medan has 26 tourist attractions grouped into five categories are natural, religious or spiritual, cultural, culinary, and recreational. Among these, four leading tourist attractions are developed and managed by the Medan City Government through the Medan City Tourism and Culture Office. These four leading attractions are Maimun Palace, Al-Mahsun Grand Mosque, Crocodile Park or Crocodile Breeding Park, and Tjong A Fie Mansion. This study uses descriptive and theoretical research. To help explain this descriptive and theoretical research, secondary data is used. The aim of this research is to explain the tourism potential of Medan City with an inclusive digital marketing approach. Research results show that inclusive digital marketing in Medan City tourism requires a marketing approach that ensures that everyone, regardless of background, identity, or ability, feels represented and respected in digital campaigns. Inclusive digital marketing involves creating inclusive messaging and visuals, ensuring accessibility, and a user-friendly experience for everyone, including people with disabilities.